Effect of metal used in resistor and inductor design for monolithic microwave integrated circuits (MMIC) applications / Elham Budi Mohd Rozali - Mohd Rozali, Elham Budi
The work highlights the design, development and fabrication of passive element for MMIC application. Different type of metals such as Aurum (Au), Platinum (Pt), and Copper (Cu) were used in the design to confer the basic characteristic of inductor (L) and resistor (R) that have been used in MMIC. The design of inductor (L) and resistor (R) were in a single turn meander inductor of 4nH and thin film resistor of 50 £1 respectively, based on microstrip theory in order to explore their performances. Analysis of the prototype using vector network analyzer of meander inductor showed that the used of various conductor strip does not affect the values of inductance. Miniaturization of the inductor and resistor were achieved with the use of highk substrate.